1982
DOI: 10.1172/jci110426
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentration in the Papillary Collecting Duct of the Rat

Abstract: A B S T R A C T Urine was observed to flow intermittently in the collecting ducts of the extrarenal papilla of antidiuretic rats. The purpose of this investigation was to test Reinking and Schmidt-Nielsen's hypothesis that intermittent flow plays an important role in the production of maximally concentrated urine. Samples of collecting duct fluid were obtained from the base and tip of the papilla by micropuncture through the intact ureter. Fluid osmolality rose sharply from base, 894±120 mosmol/kg H20-' (mean±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
1
21
1
Order By: Relevance
“…Removal of the ureter would abolish intermittent flow and impair papillary hypertonicity. If the portion of the ureter overlying the papilla is paralyzed but not removed, however, urinary osmolality does not fall, even though intermittent flow in papillary structures is abolished (1). Thus, it is the intactness of the pelvic ureter rather than its contractility that is key to its contribution to papillary hypertonicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of the ureter would abolish intermittent flow and impair papillary hypertonicity. If the portion of the ureter overlying the papilla is paralyzed but not removed, however, urinary osmolality does not fall, even though intermittent flow in papillary structures is abolished (1). Thus, it is the intactness of the pelvic ureter rather than its contractility that is key to its contribution to papillary hypertonicity.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that if the ureter is severed just beyond the tip of the renal papilla, urinary osmolality falls (1); this suggested that exchange of either water or solute between urine and renal parenchyma in the renal pelvis subserves urinary concentration. In 1966, Gertz et al (2) reported evidence for exchange of water and solute across the papillary epithelium between the papilla and an artificial fluid superfusing the renal pelvis.…”
Section: Introductionmentioning
confidence: 99%
“…While several experiments support this conclusion (Gertz et al, 1966;Schmidt-Nielsen et al, 1970, 1980) the magnitude of urea or water reentry from pelvis to papillary interstitium has never been quantified. Recently developed techniques to measure CD fluid composition through the intact ureter (Oliver et al, 1982) should be able to determine the difference in osmolarity between the fluid in the papillary CD and in the pelvis. A comparison of these measurements with the predictions of the present simulation studies would allow conclusions about the nature of the pelvic reabsórbate and its role for the concentrating mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that this architecture is identical in rat and rabbit (Section 2.2). 2) Recent direct and indirect evidence for the importance of high pelvic urea concentrations and its possible (but not proven) reflux into the medullary interstitium (Bonventre et al, 1978Schütz and Schnermann, 1972;Gertz et al, 1966;Schmidt-Nielsen et al, 1970,1980Oliver et al, 1982). High pelvic urea concentrations have been measured in rat and rabbit; in all mammalian species, the papilla is surrounded by the pelvic cavity (Kriz, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the volume flow rate emerging from the final collecting duet into the pelvis» exceeds a certain bound [36]:…”
mentioning
confidence: 99%